Optimization of chemical injection in water treatment for floating production storage and offloading units using lean six sigma methodology - Silva, Erik Felipe Luciano; Goussain, Blaha Gregory Correia dos Santos (Brazilian Journal of Operations & Production Management, 2025)
Goal: To optimize the chemical dosing process in the water treatment system of an FPSO unit by applying Lean Six Sigma methodology to reduce excessive consumption and associated financial penalties. Design/Methodology/Approach: This study applies the DMAIC methodology, using data from an FPSO unit in the Sapinhoá field, Santos Basin. The research includes statistical analysis, process mapping, and the use of cause-and-effect diagrams to identify inefficiencies and propose corrective actions. Results: The implementation of improvements resulted in a 40% reduction in oxygen scavenger consumption and a 24% decrease in the use of cleaning chemicals for sulfate removal membranes. Additionally, financial penalties due to excessive chemical consumption were reduced by approximately R450,000. Limitations of the investigation: The study focuses on operational inefficiencies rather than potential design flaws in the system. The long-term effects of the implemented improvements require continuous monitoring. Practical implications: The findings provide a structured approach for optimizing chemical dosing, enhancing operational efficiency, and reducing costs in offshore oil production units. The methodology can be adapted to similar industrial applications. Originality/Value: This study contributes to the oil and gas sector by demonstrating the effectiveness of LSS tools in optimizing chemical dosing systems, reducing operational costs, and improving overall process efficiency.